Woman’s Language Character in Against Patriarchy Hegemony In the Latest 18’s Novels - Balango, Mery (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
Woman’s language is utilized to communicate and express her ideas. Woman’s language is treated different from man. It is based on how culture perceives biological sex differences.This research conducted because of the writer's interest in the main character, firstly because the novels depicts the gender injustice that befell the female character. The second reason, because this novel depicts woman who has a fighting spirit to fight for her rights, dare to argue and then the woman character rebels against what is experienced. Feminism is a movement and ideology dedicated to achieving women's rights in order to build a world that is more than just social equality for women (Humm: 406). Feminism's ideology fights for women's rights to higher education and employment in male-dominated fields. They are also entitled to maternity leave and fair pay at work. Radical Feminism, Liberal Feminism, Marxist Feminism, Socialist Feminism, and Post- feminism are examples of feminist movements. This study is analyzing Woman’s language character of the latest 18’s novels, about how race and gender discrimination reflected by using feminist approach. The objective of the study is to analyze the novels based on its structural elements and analyze the text based on feminist approach. The data source are literary data. Those are the primary data is taken from the Novels itself and the secondary data sources are other in formations that are relevant to the subject matter. The method of the data collection is library research. The techniques of data analysis is descriptive analysis.